Varicella Zoster Encephalitis in an Immunocompetent Traveler - Bomfim, Erika Yuki Mogami; Silva, Bárbara Lopes da; Boas, Carina Ferlin Saccomani Vilas; Mattos, Aimee Elizabeth Correa Alves de; Shinoda, Bárbara Redondo; Veiga, Ana Paula Rocha; Campeas, Alexandre Ely (Brazilian Journal of Case Reports, 2026)
Varicella-zoster virus (VZV) is a frequent cause of encephalitis in adults, particularly in elderly and immunocompromised individuals. In young immunocompetent patients without cutaneous manifestations, it represents a rare presentation. We report the case of a 35-year-old previously healthy man who developed VZV encephalitis during a ten-month trip across Latin America. While in Nicaragua, he presented with bitemporal and left suboccipital headache, pulsatile in nature, insidious in onset, daily, and with progressive worsening. After five days, he sought medical care due to language disturbance (paraphasia). He denied fever, seizures, paresis, or systemic symptoms. Physical examination revealed only language impairment, with no skin lesions. Magnetic resonance imaging demonstrated hyperintensity in the left temporal lobe. Cerebrospinal fluid analysis showed hypoglycorrhachia, hyperproteinorrhachia, and hyperlactatorrhachia. Molecular testing (PCR) detected VZV DNA. Intravenous acyclovir was initiated for eight days, followed by oral acyclovir for six days, resulting in complete resolution of symptoms without residual deficits. Investigation for immunodeficiency, including HIV testing, lymphocyte immunophenotyping, immunoglobulin levels, and complement assessment, was negative. As prophylaxis, vaccination with the recombinant inactivated herpes zoster vaccine was recommended. This case illustrates an atypical presentation of VZV encephalitis, reinforcing the importance of molecular testing in the investigation of acute neurological syndromes and of early antiviral treatment for a favorable prognosis.